An International Perspective on Topics in Sports Medicine and Sports Injury 2012
DOI: 10.5772/25804
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Strategies in the Prevention of Sports Injuries From Physical Activity

Abstract: Hard cover, 534 pagesPublisher InTech

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Shoulder problems and pain have been reported by handball players in relatively high numbers (32–52%), leading to absence from the game in 36% of cases or forcing them to modify training in 68–75% [1, 5, 23]. Therefore, it has been suggested that shoulder pain should warrant undertaking special measures, including injury and overuse monitoring during both training, matches and tournaments, and implementing prevention strategies [4, 29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoulder problems and pain have been reported by handball players in relatively high numbers (32–52%), leading to absence from the game in 36% of cases or forcing them to modify training in 68–75% [1, 5, 23]. Therefore, it has been suggested that shoulder pain should warrant undertaking special measures, including injury and overuse monitoring during both training, matches and tournaments, and implementing prevention strategies [4, 29].…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates that although not every athlete is at risk, a significant number are. Therefore, this population should be monitored more closely by the medical team with the consideration of introducing preventive and therapeutic measures [4, 16, 17, 21]. Several studies suggest introducing an injury risk modification program.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, corresponding findings are only rudimentary, and often confused (Hildebrandt et al, 2012). Since the warm-up phase before athletic activity is said to lead to an increase of body temperature and metabolic rate (Casáis and Martínez, 2012), the following is to examine the extent to which IRT can be used to diagnose the SST changes in the chest region after a 10-minute warm-up, and to estimate the effects of ergometer training on general vs. local muscular warming.…”
Section: Introductionmentioning
confidence: 99%